CONTRIBUTION OF AFFORESTATION TO SUSTAINABLE LAND MANAGEMENT IN UKRAINE - Maria Nijnik; Arie Oskam; A. Nijnik (European Regional Science Association (ERSA), 2005)
This paper focuses on the establishment of forest plantations on bare lands and marginal agricultural lands: a multifunctional afforestation programme for Ukraine is elaborated. The multiple forest functions are limited in this research to wood production and erosion prevention. Ukraine is faced with erosion on 35% of its arable lands. Some 20 million ha of lands are experiencing various stages of erosion, and it is increasing with time. Erosion is especially harmful in the Carpathian Mountains where it causes windthrows and floods, and in the Steppe zone where it results in blowing up sands. Along with exploration of the expanded timber supply from the newly created forest plantations, soil protection forest functions therefore are examined. The proposition that forest cover affects the rates of soil erosion is tested empirically by means of regression analysis. The results of the estimations show a statistically significant negative relationship between soil erosion and forest cover in Ukraine and across the forestry zones. Using the results of the analysis, indicative estimates of the soil protection role of the forests are computed. Further discussion focuses on the proposed expansion of forest cover and on the potential positive effects for agriculture due to erosion prevention. Calculations have been made at different levels of detail. By using a simulation technique and cost-benefit analysis, in combination with LP modelling, it is revealed that for the discount rate of 4%, planting trees on bare lands, except in the Polissja and the Crimea, is an economically efficient means to address wood production and erosion prevention. Results are highly dependent on the relevant discount rate. For marginal agricultural lands mixed results are obtained. Moreover, there is a difference between estimated benefits for agriculture and benefits for the planter of the trees. It seems therefore necessary that e.g. the government balances costs and benefits to provide incentives for the planter of the trees. Finally, the research comes up with some practical suggestions for forest management decisions.
Keywords: 330